2022
DOI: 10.1177/01423312221123956
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-time robust trajectory tracking control for quadrotor UAV with disturbances

Abstract: Trajectory tracking control of nonlinear system with disturbances has been extensively investigated. A novel fixed-time robust trajectory tracking control scheme for quadrotor unmanned aerial vehicle (UAV) with disturbances is proposed in this paper. First, the quadrotor system is split into position and attitude loops. With the purpose of restraining coupling disturbances on position loop forced by imperfect attitude tracking, a novel fixed-time unknown input observer (UIO) is devised to accurately estimate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The ADRC, which has an Extended State Observer(ESO), can online estimate and compensate the internal and external disturbances [18]. The effectiveness of the ESO can be found in the following references ( [19]- [24]. For example, a fixed-time ESO was given in [19] to observe the unmeasurable velocity and unknown external disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ADRC, which has an Extended State Observer(ESO), can online estimate and compensate the internal and external disturbances [18]. The effectiveness of the ESO can be found in the following references ( [19]- [24]. For example, a fixed-time ESO was given in [19] to observe the unmeasurable velocity and unknown external disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the ESO can be found in the following references ( [19]- [24]. For example, a fixed-time ESO was given in [19] to observe the unmeasurable velocity and unknown external disturbances. Liu et al suggested a nonlinear adaptive backstepping controller with ESO for trajectory tracking of a QUAV subject to multiple disturbances in [20].…”
Section: Introductionmentioning
confidence: 99%